Impact of Bifidobacterium longum1714® on maternal cytokine response in peripheral blood mononuclear cells - Killeen, Sarah Louise; Mealy, Grace; Brennan, Kiva; Cotter, Paul D.; Yelverton, Cara; Saldova, Radka; Groeger, David; VanSinderen, Douwe; Doyle, Sarah; McAuliffe, Fionnuala M. (Cytokine (Philadelphia, Pa.), 2024)
•Cellular responses to PAMPs are scarcely reported longitudinally in pregnancy.•Microbiome-induced immune alterations may be implicated in pregnancy complications.•This study examined the effect of maternal probiotic supplementation on PBMC derived cytokines.•B. longum 1714 supplementation did not alter cytokine production by maternal PBMCs. The maternal immune system is implicated in adverse pregnancy outcomes. Manipulation of maternal immune response by probiotics holds potential to reduce pregnancy complications. The MicrobeMom2 study investigates the impact of probiotic supplementation on maternal immune responses to pathogen associated molecular patterns (PAMPs) in peripheral blood mononuclear cells (PBMCs) during pregnancy. This double-blinded randomised-controlled trial involved oral supplementation of Bifidobacterium longum subsp. longum 1714® (B. longum 1714; daily ingestion of a minimum of 1x109 colony forming units) or placebo from 16 to 20-weeks’ gestation until delivery in healthy pregnant women. The primary outcome was a change in IL-10 production, after stimulation with Lipopolysaccharide (LPS) or anti-CD3/28/2, in PBMCs isolated from blood samples taken at baseline (11–15 weeks’ gestation) and late pregnancy (28–32 weeks’ gestation) after 48 h incubation. 68 subjects were needed (34ineachgroup) for 80 % power at an alpha significance of 0.05 to detect differences in IL10. 72 women (mean ± SD age 33.17 ± 4.53 years and median (25th, 75th centile) body mass index 24.93 (21.93, 27.57 kg/m2)) were recruited with primary outcome data. Using LPS, late pregnancy fold change in IL-10 in PBMCs after 48 h incubation was median (25th, 75th centile) 88.45 (4.88, 488.78) in the intervention, 24.18 (6.36, 141.17) in the control group, p = 0.183. Using anti-CD3/28/2, values were 189.69 (425.96, 866.57),148.74 (31.67, 887.03) in intervention and control groups, respectively, p = 0.506. No significant differences were observed between the two groups. Maternal antenatal supplementation with B. longum 1714 did not alter cytokine production by maternal PBMCs in response to PAMPs or anti-CD3/28/2. Trial registration number: ISRCTN registry ISRCTN43013285.